Determination of gel content by incorporating imidazolium based ionic liquid as a co-solvent for epoxidized natural rubber (ENR) / Yusniwati Mohamed Yusof - Yusniwati, Mohamed Yusof (2016)

(untitled)
Epoxidized natural rubber (ENR) exhibits high gel properties where the sample preparation part is being restricted by the use of suitable solvent for dissolution process prior to the instrumental analysis. Two types of ENR (ENR 25 and ENR 50) were dissolved in organic solvent with the addition of ionic liquid (IL) that acts as a co-solvent. Two types of imidazolium based ILs namely 1-butyl-3-methylimidazolium chloride (BmimCl) and 1-ethyl-3-methylimidazolium acetate (EmimAc) were used in this study. The changes in gel composition in ENR with the incorporation of IL were monitored through gel content analysis. ENR 25 and ENR 50 were soaked in different solvents have demonstrated quite similar mean percentage of macro gel that ranging from 42.07 % to 45.19 %. The increasing values of macro gel were observed for ENR 25 dissolved in THF and BmimCl (ENR 25+THF+BmimCl) as compared to ENR 25 dissolved in THF (ENR 25+THF). There are no significant changes of the macro gel values of ENR 50+THF+BmimCl to compare with ENR 50+THF. Both ENR 25 and ENR 50 which were dissolved in THF+EmimAc have showed lower macro gel values after the third leaching cycle. The macro gel value with large standard deviation between replication was obtained for ENR 50+THF+EmimAc due to inefficient leaching process. It was observed that the incorporation of BmimCl and EmimAc during gel content determination was unable to reduce the gel content in ENR, however species other than epoxide such as trans-diol and furan were found.